Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1088/1748-9326/abdb5b
|View full text |Cite
|
Sign up to set email alerts
|

Risk and vulnerability of Mongolian grasslands under climate change

Abstract: Climate change is projected to increase the aridity of semi-arid ecosystems, including Mongolian grasslands (MG), which provide ecosystem services that support food supply and pastoralist lifestyle. Here, we conducted a grid-scale (0.5° × 0.5°) probabilistic risk assessment of MG under climate change for 40 years (1976–2015) based on probability theory. We evaluated changes of risk (impacts) and vulnerability of MG to drought between the recent two decades R20 = 1996–2015 and the previous two decades P20 = 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…For example, high temperature and low rainfall were observed in 2007, 2009, 2010, and 2017, which inevitably brought about low NPP values for Mongolian rangelands (Figure 5b-d). Some studies have mentioned that droughts' influences certainly led to a decrement in NPP [84][85][86][87]. Recent research has also confirmed that Mongolia has experienced frequent droughts [24] and warming over the last two decades, which has reduced aboveground biomass by 20% to 65% [87].…”
Section: Inter-annual Variations In Nppmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, high temperature and low rainfall were observed in 2007, 2009, 2010, and 2017, which inevitably brought about low NPP values for Mongolian rangelands (Figure 5b-d). Some studies have mentioned that droughts' influences certainly led to a decrement in NPP [84][85][86][87]. Recent research has also confirmed that Mongolia has experienced frequent droughts [24] and warming over the last two decades, which has reduced aboveground biomass by 20% to 65% [87].…”
Section: Inter-annual Variations In Nppmentioning
confidence: 98%
“…5b-d). Some studies have mentioned that droughts' influences certainly led to a decrement in NPP [84][85][86][87]. Recent research has also confirmed that Mongolia has experienced frequent droughts [24] and warming over the last two decades, which has reduced aboveground biomass by 20% to 65% [87].…”
Section: Inter-annual Variations In Nppmentioning
confidence: 98%
“…Mongolia is already experiencing a 2°C temperature increase since 1963 71 , and will likely exceed TSI-induced temperature uctuations in the near-future. Previous studies have shown a rapid loss of lakes 52 , melting mountain ice 72 , persistent soil moisture de cits 73,74 , and an increased frequency of droughts 73,75,76 and heavy rainstorms 15,77,78 . Increased rainfall may not counteract the impact of rising temperatures.…”
Section: Climate Impact On Human History In Mongoliamentioning
confidence: 99%
“…Sustained humid conditions likely enabled the expansion of fertile grasslands and thus, increased ecosystem carrying capacity 14,17,54 -allowing to raise larger numbers of livestock and horses for both meat and dairy production 9,11 . Particularly in the dry and seasonal steppe environment, domestic livestock herds experience "economies of scale" -wherein smaller herds are more vulnerable to loss from disease, predation, or weather, and larger herds are more resilient 55 .…”
Section: Climate Impact On Human History In Mongoliamentioning
confidence: 99%
“…Over recent decades, dust events have become increasingly severe in Mongolian TGs because of the combined effects of climate change and human-induced land degradation (Kurosaki et al, 2011;Nandintsetseg and Shinoda, 2015;Nandintsetseg et al, 2021). However, the occurrence of dust storms in northern China has been decreasing in recent years owing to climate change (Wang et al, 2008;Zhu et al, 2008;Liu et al, 2020) and dust storm-control projects (Wang et al, 2010;Wu et al, 2013;Tan and Li, 2015).…”
Section: Introductionmentioning
confidence: 99%